Hierarchical MoS2-carbon porous nanorods towards atomic interfacial engineering for high-performance lithium storage - Li, Zhenyou; Ottmann, Alexander; Sun, Qing; Kast, Anne; Meyer, Hans-Peter; Backes, Claudia; Schröder, Rasmus R.; Vaynzof, Yana; Klingeler, Rüdiger (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
Hierarchical nanostructures have attracted considerable attention for rechargeable battery systems since they combine the benefits of size effects induced by nanoscaling with the integrity of bulk materials. Despite significant progress, the hierarchical structures reported so far are designed only down to the nanoscale. To improve the battery performance, downsizing the designed building blocks of the hierarchical structure to smaller scales (molecular or even atomic level) is essential. This novel concept has been realized in a MoS2/C composite system, where MoS2 and N-doped carbon molecular layers are alternately stacked to form nanosheet building blocks, which are further assembled into a porous nanorod structure. This hierarchical heterostructure converts the guiding principle of sub-nanoscale engineering into practice, aiming at increasing the interfaces between MoS2 and carbon towards the largest possible molecular contact level. The resultant MoS2/N-doped carbon porous nanorods (MoS2/NC-PNR) electrode exhibits outstanding performances in lithium-ion batteries including high initial discharge capacity of ∼1300 mA h g−1, cycling stability for 700 cycles and excellent rate performance (443 mA h g−1 at 10C). The outstanding performance of the MoS2/NC-PNR superstructure illustrates the enormous potential of the hierarchically designed 2D compounds from molecular layer level, which could be extended to other layered materials.
Gesehen am 05.06.2019
Im Titel ist "2" tiefgestellt